2008
DOI: 10.1128/jb.01332-07
|View full text |Cite
|
Sign up to set email alerts
|

The Two Chorismate Mutases from both Mycobacterium tuberculosis and Mycobacterium smegmatis : Biochemical Analysis and Limited Regulation of Promoter Activity by Aromatic Amino Acids

Abstract: Chorismate mutase (CM) catalyzes the rearrangement of chorismate to prephenate in the biosynthetic pathway that forms phenylalanine and tyrosine in bacteria, fungi, plants, and apicomplexan parasites. Since this enzyme is absent from mammals, it represents a promising target for the development of new antimycobacterial drugs, which are needed to combat Mycobacterium tuberculosis, the causative agent of tuberculosis. Until recently, two putative open reading frames (ORFs), Rv0948c and Rv1885c, showing low seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 55 publications
0
13
0
2
Order By: Relevance
“…RHA1, and nfa49960 (57 %) of Nocardia farcinica IFM 10152. CM0819 also showed sequence similarity to functionally identified CMs, the highest similarity being to the recently identified cytoplasmic MtbCM (encoded by Rv0948c, identity 57 %) (Schneider et al, 2008), and to previously identified EcCM from E. coli (27 %), MjCM from M. jannaschii (10.7 %), ScCM from S. cerevisiae (9.4 %), HpCM from H. polymorpha (7.9 %), and AtCM3 from A. thaliana (7.4 %). An alignment of the deduced CMs and the structurally characterized E. coli CM revealed a range of conserved amino acid residues (data not shown).…”
Section: Bioinformatic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…RHA1, and nfa49960 (57 %) of Nocardia farcinica IFM 10152. CM0819 also showed sequence similarity to functionally identified CMs, the highest similarity being to the recently identified cytoplasmic MtbCM (encoded by Rv0948c, identity 57 %) (Schneider et al, 2008), and to previously identified EcCM from E. coli (27 %), MjCM from M. jannaschii (10.7 %), ScCM from S. cerevisiae (9.4 %), HpCM from H. polymorpha (7.9 %), and AtCM3 from A. thaliana (7.4 %). An alignment of the deduced CMs and the structurally characterized E. coli CM revealed a range of conserved amino acid residues (data not shown).…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…Chorismate mutases (CMs, EC 5.4.99.5) are of interest for bioindustry and medicine, because the enzyme is the target to improve production of aromatic amino acids such as Lphenylalanine (Phe) and L-tyrosine (Tyr) (Chavez-Bejar et al, 2008;Yakandawala et al, 2008) as well as being a putative new drug target against deadly diseases such as tuberculosis (Qamra et al, 2006;Schneider et al, 2008). CMs catalyse the conversion of chorismate to prephenate, a reaction also known as the Claisen rearrangement, and the only naturally occurring Claisen reaction in the primary metabolism of living organisms (Krappmann et al, 1999;Sugimoto & Shiio, 1980a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These structural differences could be exploited in the development of novel inhibitors targeted more specifically toward M. tuberculosis and other pathogenic mycobacteria. The results presented here provide a solid foundation to carry out genetic studies (16) to demonstrate the role, if any, of cmk in M. tuberculosis survival in the human host. …”
mentioning
confidence: 99%
“…A similar strategy can be applied to control parasites as anti-malarial agents. [5][6][7][8][9] In this study, to facilitate the production of metabolic intermediates of pharmaceutical significance in the SKA pathway, immobilization of the membrane fraction of G. oxydans IFO 3244, having the ability to catalyze oxidative fermentation from quinate to DSA, was examined. Immobilization of the cytoplasmic asymmetric reduction system composed of SKDH and GDH was also examined to identify the best carrier for SKA formation from DSA.…”
mentioning
confidence: 99%